The combined effect of transient wind‐driven upwelling and eddies on vertical nutrient fluxes and phytoplankton dynamics along Ningaloo Reef, Western Australia. Issue 7 (22nd July 2016) - Zhang, Zhenlin; Lowe, Ryan; Ivey, Greg; Xu, Jiangtao; Falter, James
Abstract: We investigate the influence of wind stresses, stratification, and coastal mesoscale eddies on upwelling intensity, vertical nutrient fluxes, and phytoplankton biomass on the continental shelf off Ningaloo Reef in northwestern Australia during an austral spring‐summer period. A three‐dimensional (3‐D) hydrodynamic model, ROMS (Regional Ocean Modeling System), was coupled with a four‐component nitrogen‐based biogeochemical NPZD model (Nitrogen Phytoplankton Zooplankton Detritus) to resolve the shelf circulation as well as the coupled nutrient and phytoplankton dynamics within a broad shelf region surrounding Ningaloo Reef. The simulated currents, temperatures, and chlorophyll a concentrations generally agreed well with both the remotely sensed satellite images and observational data collected during a field experiment from September to November 2010. Scenario tests for an individual wind‐driven upwelling event under a variety of hypothetical physical forcing conditions showed that shelf currents and biogeochemical variables were largely a function of wind stress and stratification. However, the functional relationships derived from this single wind event could not be extrapolated to other periods of the upwelling season, due to the additional influence of 3‐D mesoscale processes on the shelf. The presence, intensification, and propagation of a coastal anticyclonic eddy during the study period strongly influenced the spatial and temporal variations in nutrient profiles, which in turn caused fluctuations in vertical nutrient fluxes that were largely independent of wind stress. These results emphasize that it is necessary to fully capture the 3‐D details of the mesoscale and submesoscale coastal dynamics to properly predict upwelling‐induced coastal phytoplankton dynamics in eddy‐intensive shelf regions such as Ningaloo Reef. Key Points: ROMS simulation captured the measured physical and pelagic processes Wind stress and stratification affect coastal upwelling and biogeochemistry Eddies influence vertical nutrient fluxes during wind‐driven upwelling